2022
DOI: 10.1038/s41598-022-17114-1
|View full text |Cite
|
Sign up to set email alerts
|

Associated bacterial microbiome responds opportunistic once algal host Scenedesmus vacuolatus is attacked by endoparasite Amoeboaphelidium protococcarum

Abstract: The interactions of microalgae and their associated microbiomes have come to the fore of applied phycological research in recent years. However, the functional mechanisms of microalgal interactions remain largely unknown. Here, we examine functional protein patterns of the microalgae Scenedesmus vacuolatus and its associated bacterial community during algal infection by the endoparasite Amoeboaphelidium protococcarum. We performed metaproteomics analyses of non-infected (NI) and aphelid-infected (AI) S.vacuola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…iron 4,5 ) and growth promoting hormones 6 by bacteria in exchange for organic carbon from the algae. Apart from many beneficial interactions, some bacteria can have negative influences on algae by being algicidal and opportunistic pathogens [7][8][9] . A recent study on the bloom-forming Phaeocystis algae revealed that its microbiomes can take both symbiotic and opportunistic modes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…iron 4,5 ) and growth promoting hormones 6 by bacteria in exchange for organic carbon from the algae. Apart from many beneficial interactions, some bacteria can have negative influences on algae by being algicidal and opportunistic pathogens [7][8][9] . A recent study on the bloom-forming Phaeocystis algae revealed that its microbiomes can take both symbiotic and opportunistic modes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…1). CV cultivation in TLC showed the presence at high abundance of Vannella (9-11%), an ameboid protist, followed by Amoeboaphelidium protococcarum (6-8%), an algal parassitoid (Hoeger et al, 2022), and as expected Chlorella (5-8%). On the other hand, CV cultures in RW showed a predominant contamination of the ciliate Sterkiella that feeds on microalgae (33-39%) which, together with the absence of Chlorella, might identify a "failed culture" respect to the inoculum introduced.…”
Section: Eukaryotic Communitiesmentioning
confidence: 51%
“…These beneficial interrelations allow higher efficiencies in the removal of organic matter and nutrients in wastewater treatment than standalone microalgal or bacterial systems [24,28,61]. However, apart from many useful interactions, some heterotrophs/saprophytes/parasites can have negative influences on the periphytic community by being algicidal and opportunistic pathogens [13,63].…”
Section: Discussionmentioning
confidence: 99%